ANALISIS KETERAMPILAN MENULIS AKSARA JAWA PESERTA DIDIK MADRASAH IBTIDAIYYAH - Wahyu Agustin, Ika; Fauziah, Muna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Writing Javanese script is an important thing for students because it is a form of increasing a sense of love for the nation's culture and also to implement a sense of holding Javanese culture which is now increasingly fading and being forgotten by the current generation. The purpose of the study was to describe the profile of Javanese script writing skills of students at MI Ma`arif NU Karangsari and to describe the supporting and inhibiting factors of Javanese script writing skills of students at MI Ma`arif NU Karangsari. This study was a qualitative study. The Javanese Script Writing Skills studied were teachers and students of class IV A. The method used was the field research method. Data collection techniques were in the form of observation, interviews, documentation and tests. Data analysis techniques used were data reduction, data presentation and drawing conclusions and verification. Based on the results of the study, it can be concluded that Javanese script writing skills at MI M`arif NU Karangsari are still low or below the Minimum Completion Criteria.